Comparison of electrical velocimetry and cardiac magnetic resonance imaging for the non-invasive determination of cardiac output - Trinkmann, Frederik; Dösch, Christina; Papavassiliu, Theano; Schönberg, Stefan; Borggrefe, Martin; Kaden, Jens; Saur, Joachim (Journal of clinical monitoring and computing, 2016)
A novel algorithm of impedance cardiography referred to as electrical velocimetry (EV) has been introduced for non-invasive determination of cardiac output (CO). Previous validation studies yielded diverging results and no comparison with the non-invasive gold standard cardiac magnetic resonance imaging (CMR) has been performed. We therefore aimed to prospectively assess the accuracy and reproducibility of EV compared to CMR. 152 consecutive stable patients undergoing CMR were enrolled. EV measurements were taken twice before or after CMR in supine position and averaged over 20 s (AESCULON®, Osypka Medical, Berlin, Germany). Bland-Altman analysis showed insufficient agreement of EV and CMR with a mean bias of 1.2 ± 1.4 l/min (bias 23 ± 26 %, percentage error 51 %). Reproducibility was high with 0.0 ± 0.3 l/min (bias 0 ± 8 %, percentage error 15 %). Outlier analysis revealed gender, height, CO and stroke volume (SV) by CMR as independent predictors for larger variation. Stratification of COCMR in quintiles demonstrated a good agreement for low values (<4.4 l/min) with bias increasing significantly with quintile as high as 3.1 ± 1.1 l/min (p < 0.001). Reproducibility was not affected (p = 0.71). Subgroup analysis in patients with arrhythmias (p = 0.19), changes in thoracic fluid content (p = 0.51) or left heart failure (p = 0.47) could not detect significant differences in accuracy. EV showed insufficient agreement with CMR and good reproducibility. Gender, height and increasing CO and SV were associated with increased bias while not affecting reproducibility. Therefore, absolute values should not be used interchangeably in clinical routine. EV yet may find its place for clinical application with further investigation on its trending ability pending.
Gesehen am 15.08.2019
Published online: 27 June 2015